2019
DOI: 10.1016/j.ultramic.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Joint non-rigid image registration and reconstruction for quantitative atomic resolution scanning transmission electron microscopy

Abstract: Aberration corrected scanning transmission electron microscopes (STEM) enable to determine local strain fields, composition and bonding states at atomic resolution. The precision to locate atomic columns is often obstructed by scan artifacts limiting the quantitative interpretation of STEM datasets. Here, a novel bias-corrected non-rigid registration approach is presented that compensates for fast and slow scan artifacts in STEM image series. The bias-correction is responsible for the correction of the slow sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Novel imaging modes, where a high number of consecutive frames are acquired with small pixel dwell times, registered and summed up have shown to overcome these limitations and a precision to locate the position of atomic columns of < 10 pm has been demonstrated. [312,313] Imaging the atomic lattice and defect structures in AHSS is one aspect, the other is its correlated elemental distribution. Especially the C distribution plays a decisive role in triggering phase transformations, but is challenging to detect it quantitatively in (S)TEM.…”
Section: Challenges Of Using Scanning Transmission Electron Microscopmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel imaging modes, where a high number of consecutive frames are acquired with small pixel dwell times, registered and summed up have shown to overcome these limitations and a precision to locate the position of atomic columns of < 10 pm has been demonstrated. [312,313] Imaging the atomic lattice and defect structures in AHSS is one aspect, the other is its correlated elemental distribution. Especially the C distribution plays a decisive role in triggering phase transformations, but is challenging to detect it quantitatively in (S)TEM.…”
Section: Challenges Of Using Scanning Transmission Electron Microscopmentioning
confidence: 99%
“…It was shown that the coherent j/FCC-matrix interfaces exhibit only a slight roughness, on the order of a few atomic layers, and appear otherwise abrupt by quantifying the local-order parameter obtained from atomic column peak intensities. [168] By removing non-linear scan distortions [313] it was even possible to measure the local strain evolution in a~2 nm narrow FCC-matrix channel, establishing that the FCC-matrix embedded in-between two adjacent j-precipitates is tetragonally distorted. This severe lattice distortion strongly affects the C solubility, which is so far only accessible by first-principles calculations, but may even affect the trapping of hydrogen in these regions.…”
Section: Challenges Of Using Scanning Transmission Electron Microscopmentioning
confidence: 99%
“…For some time now, a number of authors have tried to detect and correct the drift effect in crystalline materials with several approaches, assuming that the images have uniform (Saito et al, 2009; Sang & LeBeau, 2014; Bárcena-González et al, 2018) or nonconstant (Berkels et al, 2012 a ; Sang et al, 2017; Ning et al, 2018; Berkels & Liebscher, 2019) drift rates. Most of them use real-space solutions needing a defect-free zone of reference in the image such as Rečnik et al (2005), Jones & Nellist (2013), and Zuo et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them use real-space solutions needing a defect-free zone of reference in the image such as Rečnik et al (2005), Jones & Nellist (2013), and Zuo et al (2014). Another major group focuses on the correction of drift in a series of frames from the same region, such as the works proposed by Saito et al (2009), Berkels et al (2012 b ), Binev et al (2012), Sang & LeBeau (2014), Ophus et al (2016), Bárcena-González et al (2016, 2017), or Berkels & Liebscher (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Jones and Nellist developed an NRR algorithm combining registration with prior knowledge of atomic features to remove scan distortions 4 . Berkels and Liebscher improved NRR to remove the bias toward the keyframe in the image series 21 . Ning et al 22 , Sang and LeBeau 2 , and Ophus and Ciston 3 use a series of images of the same sample area acquired with different scan directions to provide additional information for NRR correction of scan distortions, leading to sub-pm precision.…”
Section: Introductionmentioning
confidence: 99%